PAX3‐NCOA1 alveolar rhabdomyosarcoma of the tongue: A rare entity with challenging diagnosis and management. Issue 11 (23rd August 2021) - Di Carlo, Daniela; Chargari, Cyrus; Scoazec, Jean‐Yves; Cotteret, Sophie; Felix, Arthur; Moalla, Salma; Temam, Stephane; Minard‐Colin, Véronique
Abstract: Alveolar rhabdomyosarcoma (ARMS) is associated with PAX3/PAX7‐FOXO1 fusion, which confers specific clinic and biologic characteristics with inferior outcomes. A minority of tumors still histologically classified as "true" ARMS lack the canonical PAX‐FOXO1 fusion but have new molecular alterations. We present the first case of PAX3‐NCOA1 ARMS with clinical data and follow‐up in a two‐year‐old girl with ARMS of the tongue and nodal extension, treated with chemotherapy, hemi glossectomy, lymph node dissection, and brachytherapy to conserve oral function and limit long‐term sequelae. Given the rarity of such variant fusion in ARMS, international collaboration is required to evaluate its prognostic value.